PROSES PEMBERIAN GANTI RUGI TERHADAP PENGADAAN TANAH UNTUK KEPENTINGAN UMUM (Lex Jurnalica, 2019)
AbstractLand is a very vital component for social sustainability, especially public land in relation to the social functions of the land it has. In this case, not infrequently the social function has logical consequences. For example, problems related to the release of private land are then used for social purposes. To obtain this land, the role of the government is very necessary because sometimes the land will be established or the building belongs to the people, so that it must go through the government, namely by revoking land rights and freeing land rights. this matter the government must be able to carry out its functions properly and correctly. This development is carried out for the prosperity of the people. The government in solving various problems relating to land, not the people must heed the principles of law but also must pay attention to social welfare, the principle of order and humanitarian principles so that the land problem does not develop into unrest which disrupts the stability of society. However, the social function of land rights is often exploited by individual authorities who have certain interests. Where in carrying out these social functions, especially from the government often ridden by certain elements realized or not realized by the government so that the people are always sacrificed their rights, and even so permitted to be considered not violating the rights to people's land by making social functions as a shield, even the people who are positioned as rights do not support the social function of the land. Keywords: Land acquisition, public interest, social function AbstrakTanah merupakan komponen yang sangat vital bagi kelangsungan sosial,khususnya tanah publik kaitannya dengan fungsi sosial tanah yang dimilikinya.Dalam hal ini, tak jarang fungsi sosial tersebut memiliki konsekuensi logis.Misalnya saja permasalahan yang berhubungan dengan pelepasan tanah pribadiuntuk kemudian dimanfaatkan bagi kepentingan sosial. Untuk memperoleh tanahini peranan pemerintah sangat diperlukan karena terkadang tanah yang akandidirikan atau bangunan tersebut adalah milik rakyat, sehingga untukmemperolehnya harus melalui pemerintahan yaitu dengan cara pencabutan hak atas tanah dan pembebasan hak atas tanah.Peranan pemerintah atas tanah dalam rangkapembangunansangatpentingsekalisehinggadalamhalinipemerintahharusdapatmenjalankanfungsinyadengan baik dan benar.Pembangunan ini dilaksanakan untuk kemakmuran rakyat. Pemerintah dalam memecahkan berbagai masalah yang berkenaan dengan tanah, bukan sajaharus mengindahkan prinsip-prinsip hukum akan tetapi juga harusmemperhatikan kesejahteraan sosial, azas ketertiban dan azas kemanusiaan agar masalah pertanahan tersebut tidak berkembang menjadi keresahan yang mengganggu stabilitasmasyarakat.Namun,fungsisosialhakatastanahseringdimaanfaatkanolehoknum-oknumpenguasayangmempunyai kepentingan-kepentingan tertentu. Dimanadalam menjalankan fungsi sosial tersebut, khususnya dari pihak pemerintahsering kali ditunggangi oleh oknum tertentu disadari maupun tidak disadari olehpemerintahsehinggarakyatselaluterkorbankanhaknya,dan bahkan dipolessedemikian rupa izinnya supaya dianggap tidak melanggar hak atas tanah rakyatdengan menjadikan fungsi sosial sebagai tameng, bahkan hak rakyat yang adadiposisikan sebagai hak yang tidak mendukung fungsi sosialnya tanah. Kata kunci : Pengadaan tanah, kepentingan umum, fungsi sosial,-fareast-font-family: "Times New Roman";mso-ansi-language:EN-US'>  Kata kunci: putusan berbasis dogmatik, teori, asas hukum